A study on the relationship between drainage basin's geomorphic parameters and streamflow characteristics - Espino, Armando N. (1987)
Developing better methods in prediction and estimation of runoff processes has been the subject of researches of hyrdologists and planners for annual maximum daily streamflow. This thesis is an effort to establish a prediction model by investigating the relationship between geomorphic parameters and runoff processes using regression and correlation analysis.
With some established criterion, the drainage network of seventeen watersheds in the Bicol Region and the Island of Catanduanes were analyzed. The watershed area, streamcount, streamlength, main channel length, and topographic factor of each watershed were measured and quantified. The precipitation volume for each sample watershed was also derived using the Thiessen polygon method. To estimate the magnitude of annual maximum daily streamflow for design periods of 2, 5, 10, 15, 20, and 25 years, the collected streamflow data of each watershed were subjected to frequency distribution.
Regression is concerned with the ability to build a statistical model which was a set of independent or predictor variables in order to estimate the expected value of some dependent variable. Here, the event magnitudes of streamflow were taken as the dependent variables. The geomorphic parameters of the watershed and the precipitation volume received by each watershed and the areal extent of forest cover were considered as the independent variables or predictor variables.
Using stepwise regression analysis, it was revealed that the existence of stream channel, their numbers and lengths which are indeces of the capacity of the drainage basin to transmit water effectively have a consistent significant relationship with maximum flows.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Diliman.
Keywords: Drainage; Runoff; Stream measurements; Watersheds -- Philippines -- Bicol region; Watersheds -- Philippines -- Catanduanes